CO2 emission heat map of Gulf Cooperation Council region using Python for Geographic Information Systems - Deshmukh, Amol Ganesh (Journal of physics. Conference series, 2024)
As part of the efforts to ensure a place in the global competitive landscape, Oman is aligning itself with sustainable development through diversified economic measures. To address the United Nations thirteenth Sustainable Development Goal (SDG) which is climate action, the stakeholders of Oman need to understand the carbon dioxide (CO2) emissions and compare the amount of CO2 with the emissions in neighbouring Gulf Cooperation Council (GCC) countries such as United Arab Emirates (UAE), Bahrain, Qatar, Kuwait, and Kingdom of Saudi Arabia (KSA). In this research, an attempt is being made to collect the CO2 emission for all these countries and show them on a web map using python programming language. The data ranging from year 1964 to 2021 is collected from CO2 and Greenhouse Gas Emissions in Comma Separated Values (csv) format. For each country, an approximate location for Capital in terms of Latitude and Longitude is taken from google maps. Using folium library of python, these locations and CO2 emission for a particular year is plotted on google map Application Programming Interface (API). The findings reveal that Oman’s CO2 emissions from fossil fuels and industry in 2022 year is 72 million tonnes which is relatively lower when compared to those of smaller GCC countries such as Qatar (101 million tonnes) and the UAE (244 million tonnes). Nonetheless, a gradual upward trend of 12 million tonnes of CO2 emissions has been observed in Oman between the years 2019 to 2022. The python program provides an easy way to visualise the CO2 emission heatmap without the need of any proprietary software or program.